THE STUDY OF PUBLIC LEVEL AWARENESS ON WASTE MANAGEMENT TO BE GOOD CITIZENS - Agustiana, Dwizky (Department of Civic Education, 2014)
The interrelationship of humans and the environment is very influential when people do not keep their environment, that is will not provide comfort to human will not even provide a good life for human beings. Based on data from the World Bank, that writers get on the internet (www.hijauku.com) Indonesia said the national solid waste production reached 151 921 tons per day. Research is research using a quantitative approach to the study of descriptive methods to study the form of random sampling. Data were obtained through questionnaires, observation, documentation studies, literature studies, and interviews as supporting data. The results showed that: (1) Knowledge Village community Karangsong about waste management in Indramayu district still did not know better waste management. (2) The level of public awareness in the village Karangsong about waste management is still low. (3) the effectiveness of facilities and infrastructure that support is still not effective, this in because of the lack of facilities and infrastructures are active and can be used properlyKeywords: Legal awareness, waste management, the Good Citizen